Ploning pag-ibig, paghihintay at pag-asa - Santos, Judy Ann.; Garcia, Dante Nico.; Lingan, Benjamin; Sebastian, Jourdan; Gonzales, Guia.; Panoramanila Pictures, Co.; GMA Records ([Manila] Panoramanila Pictures, 2008)
Ploning, is a story of one man's search for the enigmatic woman, who has deeply wounded him in the past. Having grown up in an illegal Taiwanese fishing vessel, Rodrigo, 30 years old, returns to the beautiful island of Cuyo and is given from sunrise to look for his "Ploning". In his search, he discovers that the woman he loved and adored as a boy is not the woman he thought he knew. Ploning has displayed her maternal love for Digo, the 6 years old Rodrigo, but is shrouded in her mysterious love and devotion for Tomas, her childhood sweetheart who left her when she was 16. This 30-year-old spinster who has held a special place amongst, a devoted friends, a caring sister and a loving maternal figure is slowly unveiled through Rodrigo's memory and an emotional meeting with Ploning's confindante, Seling. Through his search, Ploning will be revealed as the island's most bittersweet source of selfless love.
Summary taken from cover.
Screenplay, Dante Nico Garcia and Benjamin Lingan ; Producers, Jourdan Sebastian and Guia Gonzales ; Executive producer, A Leenks, Inc. ; Co-producers, Judy Ann Santos, R.C. Gatmaitan, Isabelita Sabado Warren, Erika Fife, Frances Lua, Jackie Fariñas, Greg Benedy, Jeffrey Goh and Edwin Lim ; Associate producers, Raymund George Fernandez and Cecil Paz.
Judy Ann Santos, Gina Pareño, Cedric Amit, Mylene Dizon, Eugene Domingo, Ketchup Eusebio, Bojong Fernandez, Ronnie Lazaro, Jojit Lorenzo, Lukas, Tony Mabesa, Spanky Manikan, Ogoy, Crispin Pineda, Ces Quesada, Meryll Soriano, Beth Tamayo, Tessie Tomas and Joel Torre.
DVD.
In Cuyonon, with Tagalog subtitles.
Philippine entry to the 81st Academy Awards Best Foreign Language Film Category ; Official selection, Paris Cinema 2008 ; Official selection, International Film Festival of India 2008 ; Official selection, Palm Spring International Film Festival USA 2009 ; Official selection, Asia Pacific Festival of First Film Singapore 2008.
Keywords: Romance -- Drama; Cuyo (Palawan) language; Feature films; Fiction films